2020
DOI: 10.1111/andr.12842
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic characteristics of epididymis based on histology, proteomic, and 3D reconstruction

Abstract: Background The epididymis is a popular research topic in urology and reproduction. Objectives To explore and identify the anatomical characteristics of the epididymis based on histology, proteomics, and 3D reconstruction of epididymal tubules. Materials and methods A 3D reconstruction of epididymal tubules was generated based on 7‐μm‐thick transverse serial sections of an epididymis. The proteins in the subcompartments of the epididymis were obtained and analyzed by non‐labeled sequential window acquisition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The corpus of the epididymis plays a pivotal role in immune functions. The comprehension of the epididymis evolved from its initial morphological and structural characterization to encompass diverse functional aspects across different regions ( Martin et al, 1902 ; Sullivan et al, 2019 ; James et al, 2020 ; Zhao et al, 2020 ). Notably, unique gene expression patterns were identified in the caput, corpus, and cauda regions through techniques such as microarray or single-cell RNA sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corpus of the epididymis plays a pivotal role in immune functions. The comprehension of the epididymis evolved from its initial morphological and structural characterization to encompass diverse functional aspects across different regions ( Martin et al, 1902 ; Sullivan et al, 2019 ; James et al, 2020 ; Zhao et al, 2020 ). Notably, unique gene expression patterns were identified in the caput, corpus, and cauda regions through techniques such as microarray or single-cell RNA sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical analysis of the human epididymis based on histology, proteomics data and 3D reconstruction had led to a subdivision of the caput, corpus and cauda into four six and ten regions respectively ( Zhao et al, 2020 ). This research revealed significant variations in protein composition within different luminal regions of the epididymis ( Dacheux et al, 2006 ).…”
Section: Regional Segmentation and Functional Differentiation In Epid...mentioning
confidence: 99%
“…Over the past few years, we have made a concerted effort to study the human epididymis using functional genomics protocols in concert with primary cell [10][11][12][13][14][15] and organoid 16 models to investigate the biology of the human organ and its response to androgens. There are multiple challenges in researching the human epididymis: first, the paucity of human tissue samples; second, the apparent lack of complete septa dividing the functional regions of the human epididymis making characterization of each region somewhat problematic (septa have been observed, [17][18][19] though their biological properties are not fully characterized); third, the dramatic diversity in structure among different individuals. Extensive morphological and anatomical studies on the human organ have provided a valuable encyclopedia of the human epididymis (reviewed in 19,20 ), however, in real-time it is often difficult to correlate this information with fresh tissue samples when histology is not possible.…”
Section: Introductionmentioning
confidence: 99%